2018
DOI: 10.28945/4019
|View full text |Cite
|
Sign up to set email alerts
|

Place Determinants for the Personalization-Privacy Tradeoff among Students

Abstract: Aim/Purpose: This exploratory study investigates the influential factors of users’ decisions in the dilemma of whether to agree to online personalization or to protect their online privacy. Background: Various factors related to online privacy and anonymity were considered, such as user’s privacy concern on the Web in general and particularly on social networks, user online privacy literacy, and field of study. Methodology: To this end, 155 students from different fields of study in the Israeli academia were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Moreover, e-commerce consumers' privacy concerns have an adverse effect on their willingness to accept and use personalized services, but not on nonpersonalized services (Sheng et al, 2008). Weinberger and Bouhnik (2018) also supported this by arguing that consumers' high privacy concerns lead them to take action to protect their personal information against online personalization services.…”
Section: Privacy Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, e-commerce consumers' privacy concerns have an adverse effect on their willingness to accept and use personalized services, but not on nonpersonalized services (Sheng et al, 2008). Weinberger and Bouhnik (2018) also supported this by arguing that consumers' high privacy concerns lead them to take action to protect their personal information against online personalization services.…”
Section: Privacy Concernsmentioning
confidence: 99%
“…Second, online service providers' collection of personal information is perceived to be reasonable when the consumer is permitted control over the data given the risks of providing personal data (Malhotra et al, 2004). Third, privacy protection behaviors can be conducted by increasing consumers' awareness of the usage of data captured online and any potential threats (Weinberger & Bouhnik, 2018). Fourth, consumers may worry about online service providers' insufficient protection against both intentional and unintentional errors in dealing with their personal information (Hong & Thong, 2013; Smith et al, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Privacy has always been a major concern associated with the commercial information technology and particularly with regard to the issue of personalization (Sutanto et al, 2013) -"the ability to provide content and services that are tailored to individuals based on knowledge about their preferences and behaviors" (Adomavicius and Tuzhilin, 2005). The trade-off between online privacy and self-disclosure was investigated in past studies (Taddicken, 2014;Weinberger et al, 2017;Weinberger and Bouhnik, 2018). Some of which focused specifically on the trade-off between online personalization and online privacy protection (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Some of which focused specifically on the trade-off between online personalization and online privacy protection (e.g. Weinberger and Bouhnik, 2018). Many of the studies showed that users are concerned with their online privacy and wish to protect it (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords music streaming applications, personal information management, privacy, personalization was investigated in past studies (Fogel & Nehmad, 2009;Hoy & Milne, 2010;Milne, Rohm, & Bahl, 2004;Paine, Reips, Steiger, Joinson, & Buchanan, 2007;Taddicken, 2014;Weinberger & Bohnik, 2018;Weinberger, Bouhnik, & Zhitomirsky-Geffet, 2017;Wills & Zeljkovic, 2011), some of which focused specifically on the tradeoff between online personalization and online privacy protection (e.g., Weinberger & Bouhnik, 2018). Many of the studies showed that users are concerned with their online privacy and wish to protect it (e.g., Paine et al, 2007;Wills & Zeljkovic, 2010).…”
Section: Introductionmentioning
confidence: 99%